Comprehensive investigation of gene mutations in canine large cell gastrointestinal lymphoma - Matsumura, Naoki; Tsuruta, Takumi; Goto-Koshino, Yuko; Mizukami, Keijiro; Aoi, Tomomi; Yamada, Ryoko; Matsumoto, Yuki; Nagao, Itsuma; Sakamoto, Megumi; Nakagawa, Taisuke; Fukuoka, Ray; Ohmi, Aki; et al. (Frontiers in Veterinary Science, 2025)
Large cell gastrointestinal lymphoma (LCGIL) is the most common extranodal lymphoma in dogs, but its molecular biological backgrounds have not been clarified. In this study, we comprehensively investigated the gene mutations in LCGIL. Whole exome sequencing analysis using four dogs with LCGIL showed mutations in NACC1 gene in two dogs. Further, the six genes known to be mutated in human intestinal T-cell lymphoma, ASXL3, SOCS3, PRDM1, FYN, TET2, and ZDBF2, were found to be mutated in one dog. Then, targeted next-generation sequencing analysis was performed to validate these results using additional 31 dogs with LCGIL. As a result, the mutation in ZDBF2 genes were identified in all samples, but the same mutation was ubiquitously observed in all peripheral blood samples. As for the remaining genes, the mutations were not observed in any dogs. The targeted next-generation analysis of whole exon regions of ZDBF2 revealed the other mutations in additional three dogs. In the present study, some mutations in genes related to human intestinal T-cell lymphoma were identified, but common gene mutations were not found among most cases. These results implied the heterogeneity of molecular pathophysiology of canine LCGIL. Further studies are needed to comprehensively analyze genomic and non-genomic molecular aberrations in each canine LCGIL case.